1989
DOI: 10.1111/1523-1747.ep12721500
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 19: Predicted Amino Acid Sequence and Broad Tissue Distribution Suggest it Evolved from Keratinocyte Keratins.

Abstract: The type I keratin 19 is unusual in its tissue distribution in that under normal circumstances it does not seem to be restricted, as the other keratins are, to expression in either stratified or simple epithelia. In addition to the previously reported distribution of keratin 19 in human tissues, we have observed keratin 19 in epidermal basal cells, in a defined region of the hair follicle, and in nipple epidermis. We noticed that expression of keratin 19 appears to be especially characteristic of regions of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(110 citation statements)
references
References 71 publications
6
102
1
1
Order By: Relevance
“…This further indicates that cytokeratin 6a expression may be maintained beyond the stem cell stage. Cytokeratin 19, which has been implicated in the differentiation of many epithelial tissues in which there is a transition between different phenotypes (Stasiak et al, 1989), was also shown to be a marker for prostatic intermediate cells and to play a key role in prostatic differentiation (Hudson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This further indicates that cytokeratin 6a expression may be maintained beyond the stem cell stage. Cytokeratin 19, which has been implicated in the differentiation of many epithelial tissues in which there is a transition between different phenotypes (Stasiak et al, 1989), was also shown to be a marker for prostatic intermediate cells and to play a key role in prostatic differentiation (Hudson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Other keratin antibodies were LE41 (K8) and LE61 (K18) (Lane, 1982), LL002 (K14) (Purkis et al, 1990), LL025 (K16) (Wilson et al, 1994), LHK6 (K6) and LHK15 (K15) (Waseem et al, 1999), LP2K (K19) (Stasiak et al, 1989) RCK102 (K5 &K8) (Broers et al, 1986), and LH2 (K10) (Leigh et al, 1993). Additional monoclonal antibodies used were E-cadherin (Transduction Laboratories, Lexington, Kentucky) diluted 1:50, 11-5F (anti-desmoplakin) (Parrish et al, 1987) diluted 1:100; and MM-1 (anti-Ki67) (Novacastra, Newcastle upon Tyne, United Kingdom).…”
Section: Antibodies Usedmentioning
confidence: 99%
“…Since cytokeratins are generally released during cell death, this suggests either that the content of cytokeratin 19 in squamous carcinoma cells is higher than in adenocarcinoma cells or that the cell loss factor is larger in patients with squamous cell carcinoma. Although cytokeratin 19 is widely distributed in epithelial tissues and generally regarded as characteristic of simple epithelia, a relation with the keratinocyte keratins has been suggested (Bartek et al, 1985;Stasiak et al, 1989). The fact that the sensitivity of TPA is also higher in patients with squamous cell carcinoma than in patients with adenocarcinoma argues against the hypothesis that the increased sensitivity is only related to squamous cell differentiation.…”
Section: Sensitivitymentioning
confidence: 99%